FEARS OF AN OPEN MARKET: CITIZENS’ VOICES OF THE ASEAN ECONOMIC COMMUNITY (AEC) - Makin, Al (LPPM IAIN Kudus, 2016)
This article presents the way in which Indonesian citizens responded to the idea of the open market in the South East Asian country established by the AEC. The article chooses some opinions published by the Indonesian media: Kompas, Dakwatuna, Koran Muria, Koran Yogya, Islam Pos, Hizbut Tahrir website, and Jawa Pos from 2014 to 2016 which show fears of and resistance against the free market. In the arguments they exhibit the fears which are motivated by the citizens’ sentiments of nationalism and religion. The article also finds that the AEC is not well understood by the citizens of Indonesia, perhaps due to the lack of socialization by the government. Indeed, the AEC documents do not show any aspects outside economy as the main enterprise of the community, such as religion and nationalism which indeed motivated the fears of the Indonesian citizens. This led to difficulty by Indonesians to accept the idea of the free market who are mostly religious and hold nationalism in high regard. This paper also presents the detailed reasons and the arguments of the fears of the free market in the South East Asia.